2020
DOI: 10.3892/ol.2020.11768
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL4 overexpression is associated with progression and poor prognosis in breast cancer

Abstract: The aim of the present study was to analyze the expression levels of angiopoietin-like 4 (ANGPTL4) in breast cancer to investigate the association between ANGPTL4 and breast cancer. Immunohistochemistry was performed on formalin-fixed paraffin-embedded tissues, including 205 invasive ductal carcinoma (IDC) of no special type, 40 normal breast, 40 atypical ductal hyperplasia (ADH) and 40 ductal carcinomas in situ (DCIS) tissues. The non-parametric Kruskal-Wallis test was used to evaluate the differential expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…A central role in cell invasion and migration through the regulation of tumor angiogenesis and vascular permeability was also demonstrated for ANGPTL4 which we found strongly upregulated in metastatic PCs compared to PAs and non-metastatic PCs (Tan et al 2012, Zhao et al 2020. In vitro experiments using a human colorectal cancer cell line suggested a novel role of ANGPTL4 as upstream regulator of the BMP7 gene, a member of the TGF-beta superfamily that plays critical roles in the control of cell growth, differentiation, migration and apoptosis in various types of cancers (Li et al 2015).…”
Section: Endocrine-related Cancersupporting
confidence: 61%
“…A central role in cell invasion and migration through the regulation of tumor angiogenesis and vascular permeability was also demonstrated for ANGPTL4 which we found strongly upregulated in metastatic PCs compared to PAs and non-metastatic PCs (Tan et al 2012, Zhao et al 2020. In vitro experiments using a human colorectal cancer cell line suggested a novel role of ANGPTL4 as upstream regulator of the BMP7 gene, a member of the TGF-beta superfamily that plays critical roles in the control of cell growth, differentiation, migration and apoptosis in various types of cancers (Li et al 2015).…”
Section: Endocrine-related Cancersupporting
confidence: 61%
“…Finally, angiopoietin-like 4 (Angptl-4), a secreted glycoprotein, has been reported as another potent marker [ 53 ]. Angptl-4 is highly expressed in the adipose tissue and liver, and is known to be associated with tumor metastasis [ 54 ]. It is reported that the expression of angptl-4 in serum and podocytes in MCNS as well as the rodent podocytes under the treatment with LPS or puromycin aminonucleoside (PAN) were increased [ 53 ].…”
Section: Biomarkers In Minimal Change Nephrotic Syndrome and Focalmentioning
confidence: 99%
“…Consistently with these reports, we found that a high level of ANGPTL4 significantly shortens the DMFS of BC patients. One study showed that ANPTL4 is an independent poor prognostic factor for the OS and diseasefree survival (DFS) of BC patients [44]. We also observed that high levels of ANGPTL4 significantly shorten the OS of BC patients.…”
Section: Discussionmentioning
confidence: 53%